ANIMAL ALLERGY AMONG HUSBANDRY PERSONNEL IN RIYADH - Maneea, Muhammad Al-; Juhaim, Saad Al; hatlan, Omar Al-; Kujan, Omar; Tarakji, Bassel; Azzegahiby, Saleh; Azzegahiby, Ibrahim; Wyse, Richard KH; Rabia, Mohammed W Al; Alenzi, Faris QB (Journal of Ayub Medical College Abbottabad, 2013)
Background: The importance of specific animal allergy in immuno-pathology of asthma and atopic diseases remained to be defined. Methods: We measured total and specific IgE. Western blotting of some allergens was also characterised. Result: There was a significant elevation of IgE in 3 persons among 15 samples collected. Western blotting showed common husbandry allergens from 3 sources that have common allergenicity. Conclusion: Exposure to animal products exacerbates allergic asthma in adults, suggesting that preventive measures should be taken to reduce their sensitivity. Keywords: Animal Allergy, IgE, RAST, Asthma